An Efficient Topology for Wireless Power Transfer over a Wide Range of Loading Conditions - Tianqing Li; Xiangzhou Wang; Shuhua Zheng; Chunhua Liu (Energies, 2018)
Although an inductive power transfer (IPT) system can transfer power efficiently in full-load conditions, its efficiency obviously decreases in light-load conditions. To solve this problem, based on a two-coil IPT system with a series-series compensation topology, a single-ended primary-inductor converter is introduced at the secondary side. By adjusting the set effective value of the current in the primary coil, the converter input voltage changes to maintain the equivalent input resistance of the converter in an optimal condition. The system can then transfer the power efficiently with the wide load conditions. Moreover, the system operates at a constant resonance frequency with a high power factor. Both the simulation and experimentation of a prototype with a 10 W IPT system demonstrate the effectiveness of the proposed topology for wireless power transfer.